Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/cvr/cvac021
|View full text |Cite
|
Sign up to set email alerts
|

Gene editing reverses arrhythmia susceptibility in humanized PLN-R14del mice: modelling a European cardiomyopathy with global impact

Abstract: Aims A mutation in the phospholamban (PLN) gene, leading to deletion of Arg14 (R14del), has been associated with malignant arrhythmias and ventricular dilation. Identifying pre-symptomatic carriers with vulnerable myocardium is crucial because arrhythmia can result in sudden cardiac death, especially in young adults with PLN-R14del mutation. This study aimed at assessing the efficiency and efficacy of in vivo genome editing, using CRISPR/Cas9 and a cardiotropic adeno-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Based on initial findings from PLN-R14del overexpression in a heterologous cell culture system as well as in the mouse heart, PLN-R14del was proposed to exert super-inhibitory effects on SERCA2a activity, leading to cardiac remodeling and early death [5]. Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on initial findings from PLN-R14del overexpression in a heterologous cell culture system as well as in the mouse heart, PLN-R14del was proposed to exert super-inhibitory effects on SERCA2a activity, leading to cardiac remodeling and early death [5]. Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, herein we assume all cardiomyocytes will need to be sufficiently restored, requiring an abundant number of therapeutic cells to be delivered (2-5 custom cells per cardiomyocyte). However, recent gene therapy studies have shown that correcting only a small percentage of cardiomyocytes can improve muscle function ( Long et al, 2016 ; Nelson et al, 2016 ; Dave et al, 2022 ). Further in vitro and in vivo validation studies are therefore warranted to explore the cell coupling efficiency required to achieve a therapeutically beneficial restoration effect.…”
Section: Discussionmentioning
confidence: 99%
“…Dave et al (2022) aimed to assess the therapeutic effects of CRISPR/Cas9-mediated genome editing on cardiac function in mice carrying a mutation in the PLN9 gene [ 69 ]. The authors employed a cardiotropic AAV9 vector to deliver CRISPR/Cas9 and guide RNA (gRNA) effectively disrupting the gene and evaluated the efficacy of the gene editing using droplet digital polymerase chain reaction and next-generation sequencing (NGS)-based amplicon sequencing [ 69 ]. The results indicated that mutant mice had bi-ventricular dilation and increased stroke volume compared to wild-type mice, with a higher propensity for sustained ventricular tachycardia [ 69 ].…”
Section: Reviewmentioning
confidence: 99%
“…The authors employed a cardiotropic AAV9 vector to deliver CRISPR/Cas9 and guide RNA (gRNA) effectively disrupting the gene and evaluated the efficacy of the gene editing using droplet digital polymerase chain reaction and next-generation sequencing (NGS)-based amplicon sequencing [ 69 ]. The results indicated that mutant mice had bi-ventricular dilation and increased stroke volume compared to wild-type mice, with a higher propensity for sustained ventricular tachycardia [ 69 ]. This is followed by in vivo gene editing to correct the induced mutation, which significantly reduced end-diastolic and stroke volumes and susceptibility to ventricular tachycardia [ 69 ].…”
Section: Reviewmentioning
confidence: 99%